2017
DOI: 10.1002/2016jb013266
|View full text |Cite
|
Sign up to set email alerts
|

Objective estimation of spatially variable parameters of epidemic type aftershock sequence model: Application to California

Abstract: The Epidemic Type Aftershock Sequence (ETAS) model is widely employed to model the spatiotemporal distribution of earthquakes, generally using spatially invariant parameters. We propose an efficient method for the estimation of spatially varying parameters, using the expectation maximization (EM) algorithm and spatial Voronoi tessellation ensembles. We use the Bayesian information criterion (BIC) to rank inverted models given their likelihood and complexity and select the best models to finally compute an ense… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 117 publications
1
68
0
Order By: Relevance
“…The algorithm developed by Nandan et al (2017) for the estimation of spatially variable parameters of an Epidemic-type aftershock sequence was modified and applied to the available TOC and 14 C data for the CMS by assuming a log-normal distribution of these parameters (Seiter et al, 2004). Previous studies have also assumed a log-normal distribution of TOC and other parameters (Diggle & Ribeiro, 2007;Gosheva et al, 2017;Nussbaum et al, 2014;Seiter et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The algorithm developed by Nandan et al (2017) for the estimation of spatially variable parameters of an Epidemic-type aftershock sequence was modified and applied to the available TOC and 14 C data for the CMS by assuming a log-normal distribution of these parameters (Seiter et al, 2004). Previous studies have also assumed a log-normal distribution of TOC and other parameters (Diggle & Ribeiro, 2007;Gosheva et al, 2017;Nussbaum et al, 2014;Seiter et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Overall, there is a strong imperative to find effective methods that deconvolve the complex patterns in OC content and composition, and to provide a mechanistic understanding of the underlying processes responsible for this heterogeneity. In this study, we apply a clustering algorithm adapted from Nandan et al (2017) as a novel way of classifying swaths of ocean floor into distinct "carbon impact" regions. We then apply statistical analyses to assess the region-specific factors impacting the carbon dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we introduced an objective method to invert spatially variable parameters of the ETAS model (Nandan et al, ). We found that the three parameters K , a , and μ show substantial spatial variation, which could be explained by the spatial variation of the surface heat flow in the study region.…”
Section: Methodsmentioning
confidence: 99%
“…We found that the three parameters K , a , and μ show substantial spatial variation, which could be explained by the spatial variation of the surface heat flow in the study region. In Nandan et al (), however, we considered the parameters of the temporal (Omori) and spatial kernels to be spatially invariant for reasons of computational and mathematical simplicity. In the present work, we have extended our previous method to invert the spatial variation of the Omori parameters as well, while still assuming the parameters of the spatial kernel to be spatially invariant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation